Role of Li+ and Fe3+ in modified ZnO: Structural, vibrational, opto-electronic, mechanical and magnetic properties - Bajpai, G.; Moirangthem, I.; Sarkar, S.; Barman, S. R.; Vinod, C. P.; Bajpai, S.; Riyajuddin, S.; Ghosh, K.; Basaula, D. R.; Khan, M.; Liu, S. -W.; Biring, S.; et al. (Ceramics International, 2019)
When Fe is doped in ZnO, a situation of charge imbalance is created due to the higher charge of Fe3+. A charge balance may be obtained by co-doping Li+0.5Fe3+0.5 combinations. A solid solution of Zn1-x(Fe0.5Li0.5)xO (0 ≤ x ≤ 0.03125) is synthesized with this viewpoint. The crystallites belong to a wurtzite P63mc space group, with lattice parameters a, b and c increasing nominally for x = 0.0156 and thereafter remaining invariant. The size varies in the range ~ 60–142 nm. Interstitials of Li and Zn ions are formed. Along with Fe3+ substitution these defects are reasons for O interstitials. These oxygen interstitials increase the red emission while reduction of oxygen vacancies reduces the green emission. These point defects create structural distortion and strain which can generate Zn vacancies. Bandgap reduces due to shallow defects. Mid-bandgap states due to oxygen interstitials and Fe 3d-O 2p hybridization result in NIR emission. On the other hand the crystal surface deforms due to Li addition which hardens the materials. A weak ferromagnetism appears at very low temperature which is enhanced by Li+ addition. Long range exchange mechanism between Fe3+ ions appears in the samples, mediated by magnetic polarons due to point defects.
Keywords: hardness; NIR emission; Shallow and deep level defects; Weak ferromagnetism; ZnO